Hubungan Kegiatan Ekstrakurikuler dengan Psychological Well-Being Mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi - Felicia A. Gunawan; Hendri Opod; Lydia E. V. David (Universitas Sam Ratulangi, 2024)
Abstract: Pre-Clinical Students tend to experience a decline in quality of life and well-being due to different responsibilities in curriculum, tasks, and demands during their studies. Extracurricular activities involve aspects of perseverance, empathy, and mindfulness, where these elements can prevent, and even enhance, an individual's psychological well-being (PWB). This study aimed to evaluate the correlation between extracurricular activities and PWB in pre-clinical medical students of Universitas Sam Ratulangi, Manado. This was a quantitative approach study employing data collection through the administration of the PWB scale (PWBS) questionnaire with 84 items developed by Ryff. The results obtained a total of 155 respondents participated in this study. The analysis did not reveal any correlation between participation in extracurricular activities and the dimensions of PWB. Albeit, a correlation was identified between the duration of involvement in extracurricular activities and specific dimensions of PWB (p<0.05). In conclusion, there is no correlation between extracurricular activities and PWB. However, there is a correlation between the duration aspect of involvement in extracurricular activities and PWB dimensions, especially the dimensions of positive relations with others and personal growth. Keywords: extracurricular activities; psychological well-being; duration aspect Abstrak: Mahasiswa Program Studi Pendidikan Dokter cenderung mengalami penurunan kualitas hidup dan kesejahteraan karena adanya perbedaan dari segi kurikulum, tugas, dan tuntutan dalam menjalani studi. Kegiatan ekstrakurikuler merupakan suatu kegiatan yang melibatkan aspek ketekunan, empati, dan mindfulness, di mana aspek-aspek ini dapat mencegah penurunan, bahkan meningkatkan psychological well-being (PWB) seseorang. Penelitian ini bertujuan untuk mengevaluasi korelasi antara kegiatan ekstrakurikular dengan PWB pada mahasiswa pre-klinik Universitas Sam Ratulangi, Manado. Jenis penelitian ialah kuantitatif dengan metode pengambilan data menggunakan kueisioner PWB scale (PWBS) 84–items oleh Ryff. Hasil penelitian mendapatkan 155 responden yang terlibat dalam penelitian ini yang mengikuti kegiatan ekstrakurikuler. Tidak ditemukan adanya korelasi antara kegiatan ekstrakurikuler dengan dimensi PWB, tetapi terdapat korelasi antara aspek durasi keterlibatan ekstrakurikuler dengan dimensi-dimensi PWB tertentu (p<0,05). Simpulan penelitian ini ialah tidak terdapat hubungan antara ekstrakurikuler dengan PWB, tetapi terdapat hubungan antara aspek durasi keterlibatan ekstrakurikuler dengan dimensi PWB, terkhususnya dimensi positive relations with others dan personal growth. Kata kunci: aktivitas ekstrakurikuler; psychological well-being; aspek durasi